Pleiotropy - cellular-molecular evolution in action - Torday, John S. (Henry Stewart Talks, 2016)
Pleiotropy as a Rubik’s Cube ('Repurposing' of genes in response to evolution), Complex physiologic phenotypes as homologs of the unicellular cell membrane, Driving factors for 'repurposing' of genes, Examples of pleiotropic 'repurposing' of genes, Aging vs. ‘antagonistic pleiotropy’, Pleiotropy as the basis for endothermy